Interpersonal behavioural problems in children with hearing impairment: the parental experiences and coping strategies - Garba, Rabiu; Badzis, Mastura (2017)
Rare studies address the experiences of parents on interpersonal behaviour problems of their children with hearing impairment in Kano state Nigeria. Children with hearing impairment often have some sort of exceedingly language disability which is a major factor affecting their interpersonal relation with their parents, peers, and family. The present research was pretensioned to probe the interpersonal behaviour problems of children with hearing difficulties as lamented by their parents. The research was a qualitative single case study in which an indepth interview was conducted with eight parents whose children were profoundly hearing impaired. A thematic analysis of the data identified three core categories: Aggression, judgement from others and seeking social support. On the basis of the research findings, it was concluded that most of the hearing-impaired children are rebellious, they exhibit rudeness, show temper outburst, destroy property and fight perpetually. Whereas, their parents turn to spiritualism and collaborate with other people to cope with the challenging experiences they have. It was emphasized, the parents of the hearing impaired themselves believed they need additional advocacy. This elevates a cardinal blueprint and finds it expedient that hearing impaired parents have found helpful. Eventually, the briefing suggests parental commitment, love and enthusiasm, whereas, governmental intervention to uplift the life of hearing impaired children was equally recommended.